2018
DOI: 10.1002/aenm.201802427
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Interactions in Bi‐Sn Bimetallic Electrocatalysts for Highly Selective Electrochemical CO2 Reduction toward Formate Production

Abstract: A highly selective and durable electrocatalyst for carbon dioxide (CO2) conversion to formate is developed, consisting of tin (Sn) nanosheets decorated with bismuth (Bi) nanoparticles. Owing to the formation of active sites through favorable orbital interactions at the Sn‐Bi interface, the Bi‐Sn bimetallic catalyst converts CO2 to formate with a remarkably high Faradaic efficiency (96%) and production rate (0.74 mmol h−1 cm−2) at −1.1 V versus reversible hydrogen electrode. Additionally, the catalyst maintains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
269
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(279 citation statements)
references
References 84 publications
9
269
1
Order By: Relevance
“…State-of-the-art electrocatalytic synthesis of FA currently is being pursued by two companies-OCO and Dioxide Materials-both of which have filed multiple patents for process that can be used to prepare and separate FA [73b, [121][122][123][124][125][126] . Before electrochemical synthesis of FA can be applied on a commercial scale, it must be demonstrated that the existing electrodes have low enough over-potential so that reduction of CO 2 to FA does not compete with the H 2 evolution reaction [33,50,127] . Recent developments in electrodes and electrolyzers-especially, novel membranes-increase the possibility of efficient and cost-effective electrochemical reduction of CO 2 to FA or FS 128,127,[129][130][131] , and the reverse dehydrogenation reaction to form FA [132] .…”
Section: Challenges and Future Of The Fa/fs Systemsmentioning
confidence: 99%
“…State-of-the-art electrocatalytic synthesis of FA currently is being pursued by two companies-OCO and Dioxide Materials-both of which have filed multiple patents for process that can be used to prepare and separate FA [73b, [121][122][123][124][125][126] . Before electrochemical synthesis of FA can be applied on a commercial scale, it must be demonstrated that the existing electrodes have low enough over-potential so that reduction of CO 2 to FA does not compete with the H 2 evolution reaction [33,50,127] . Recent developments in electrodes and electrolyzers-especially, novel membranes-increase the possibility of efficient and cost-effective electrochemical reduction of CO 2 to FA or FS 128,127,[129][130][131] , and the reverse dehydrogenation reaction to form FA [132] .…”
Section: Challenges and Future Of The Fa/fs Systemsmentioning
confidence: 99%
“…[ 6 ] Another alternative low‐cost catalyst of Bi possesses some characteristics that are suitable for CO 2 electrochemical reduction. [ 1h,7 ] Recently, several studies reported the unique properties of Sn‐Bi eutectic alloys, [ 8 ] the orbital interaction effects at the interface between Sn nanosheets and Bi nanoparticles (NPs), [ 9 ] and amorphous SnO x modified by Bi species, [ 10 ] which are promising candidates for CO 2 reduction. Nonetheless, the problems of low formate selectivity and high competition with hydrogen evolution at low overpotentials remain unsolved.…”
Section: Figurementioning
confidence: 99%
“…The observed binding energy of Sn species in the Sn 0.80 Bi 0.20 alloy NPs are slightly larger than those for the Sn NPs (Figure S12, Supporting Information), while the values for Bi are slightly smaller than the reported values. [ 9,13 ] These are due to the charge transfer between Sn and Bi or band bending across the core–shell junctions. [ 5a ] The surface compositions obtained from XPS agree with the ICP‐MS results (Table S2, Supporting Information), indicating the uniform distribution of Sn and Bi elements in the whole Sn 0.80 Bi 0.20 core–shell NPs.…”
Section: Figurementioning
confidence: 99%
“…Among the metal oxide electrocatalysts, SnO 2 has shown the excellent performance for the conversion of CO 2 to HCOOH. Various strategies including surface modification, construction of heterostructure, and introduction of surface strain, grain boundaries et al. have been investigated to further improve the activity and selectivity of SnO 2 for CO 2 reduction.…”
Section: Figurementioning
confidence: 99%